"Inflammaging" as a Druggable Target: A Senescence-Associated Secretory Phenotype—Centered View of Type 2 Diabetes. (1st June 2016) - Prattichizzo, Francesco; De Nigris, Valeria; La Sala, Lucia; Procopio, Antonio Domenico; Olivieri, Fabiola; Ceriello, Antonio
Abstract : Aging is a complex phenomenon driven by a variety of molecular alterations. A relevant feature of aging is chronic low-grade inflammation, termed "inflammaging." In type 2 diabetes mellitus (T2DM), many elements of aging appear earlier or are overrepresented, including consistent inflammaging. T2DM patients have an increased death rate, associated with an incremented inflammatory score. The source of this inflammation is debated. Recently, the senescence-associated secretory phenotype (SASP) has been proposed as the main origin of inflammaging in both aging and T2DM. Different pathogenic mechanisms linked to T2DM progression and complications development have been linked to senescence and SASP, that is, oxidative stress and endoplasmic reticulum (ER) stress. Here we review the latest data connecting oxidative and ER stress with the SASP in the context of aging and T2DM, with emphasis on endothelial cells (ECs) and endothelial dysfunction. Moreover, since current medical practice is insufficient to completely suppress the increased death rate of diabetic patients, we propose a SASP-centered view of T2DM as a futuristic therapeutic option, possibly opening new prospects by moving the attention from one-organ studies of diabetes complications to a wider targeting of the aging process.